Cappadocia: The Effects of Tourist Motivation on Satisfaction and Destination Loyalty - Faruk Seyitoğlu (Journal of Tourismology)
The present study investigates how the motivations of foreign tourists visiting the Cappadocia region in Turkey affect their satisfaction and destination loyalty. The research was conducted using a questionnaire, which was answered by 363 foreign tourists visiting Cappadocia. First, the main factors in tourists’ motivation for travel were determined. These motivation factors and satisfaction and destination loyalty intention scales were used to conduct multiple regression analyses. The results suggest that three categories of tourist motivations (‘novelty and learning’, ‘escape and relaxation’, and ‘socialization’) had a direct correlation with satisfaction, while two (‘novelty and learning’ and ‘escape and relaxation’) had a direct correlation with destination loyalty. This work has implications for destination managers and tourism businesses, and we conclude with suggestions for future studies.